Economic determinants of success in Olympic Games - Makiyan, S.-N.; Rostami, M. (Turkish Journal of Sport and Exercise, 2021)
Sport economics is defined as the application of economic theories for analyzing of sport activities in which Olympic Games are the most famous ones. Activities in such games are measured by the number of medals that a certain country obtains. One way to predict medals winning by countries is to consider economic strength of the country in addition to the abilities of athletics. In this study, the effect of the most important economic factors on medals winning, such as Population, GDP per capita, and also hosting and the experience from past times in Olympics as explanatory variables are considered, which have not been reflected so far in the related studies. These variables are appropriate for the assessment of the potential of countries` success in Olympics. The data which is used, is in form of discrete data. Accordingly, Poisson Regression model is suitable for the purpose of this study. The period of examination is from 1992-2016 for evaluating the availability of having more medals in Olympics. The results, indicate a positive and significant relationship between economic factors, hosting and experiences in Olympic progressing. Since, countries expect from Olympics Games to derive more medals after the use of their resources, which have been allocated for this purpose, the study suggests that success in the Olympic need to consider the importance of economic factors.